Kajian Hukum atas Penelantaran Aset Daerah untuk Kepentingan Investasi oleh Pihak Ketiga - Khairus Febryan Fitrahady; Budi Sutrisno; Ahmad Zuhairi (Faculty of Law Hang Tuah University, 2022)
This research is to examine the protection and legal standing of the local government for abandoning regional assets for investment purposes by third parties or investors. The research method used is normative legal research using statutory and conceptual approaches. Based on the results of the study that the utilization of regional assets for investment purposes must be maximized by investors, these assets are important for increasing regional original income by local governments. Regional governments have the authority and strategic position to decisively terminate contracts with investors who have clearly failed to utilize regional assets for investment purposes. With the principle of exeptio non admplenti contractus, the regional government can terminate the contract unilaterally to investors who do not first fulfill the achievements as promised.